Energy - economic efficiency and private-sector participation : key elements in power sector recovery. (1993)
Examines the main problems facing the sector, and presents forecasts for demand, supply and investment requirements. Identifies and analyzes the principal options for a strategy that could contribute to solving investment financing problems and, thereby, to ensuring electricity supplies at the regional level.
DC